Pulmonary vascular dysfunction in refractory acute respiratory distress syndrome before veno‐venous extracorporeal membrane oxygenation. Issue 4 (19th October 2015) - Lazzeri, C.; Cianchi, G.; Bonizzoli, M.; Batacchi, S.; Terenzi, P.; Bernardo, P.; Valente, S.; Gensini, G. F.; Peris, A.
Abstract : Background: Pulmonary vascular dysfunction has been described in patients with acute respiratory distress syndrome (ARDS). Veno‐venous extracorporeal membrane oxygenation (VV‐ECMO) is a well‐established treatment for these patients. We hypothesized that severe pulmonary vascular dysfunction and cor pulmonale identified by echocardiography before cannulation in these patients were associated with worse survival. Methods: Echocardiography was used to identify pulmonary hypertension in 21 patients with refractory ARDS just before ECMO implantation. Survival was compared for those with and without cor pulmonale. Results: In our series, the overall mortality rate was 57.1% (12/21). Echocardiographic exams were transthoracic in 5 patients (23.8%), transesophageal in 4 patients (19%), and both (transthoracic and transesophageal) in the remaining 12 patients (57.1%). In our series, six patients (28.5%) showed LV dysfunction. Acute cor pulmonale was detectable in 2 patients (9.5%), while the remaining 19 patients showed moderate pulmonary dysfunction. Survivors had a higher pre‐cannulation LV ejection fraction (EF) ( P = 0.02) and tricuspid annular plane excursion ( P = 0.04), and lower peak systolic pulmonary artery pressures ( P = 0.02). Conclusions: In patients with refractory ARDS immediately before ECMO implantation, the prevalence of acute cor pulmonale is low (9.5%). Survival is associated with higher LVEF and lower systolic pulmonary arterial pressure. These findings support the idea that echocardiographic assessment of pulmonary artery pressure in patients with refractory ARDS before VV‐ECMO implantation may have value for risk‐stratification.